Pengaruh Media Pembelajaran Talking Stick Terhadap Hasil Belajar Siswa Kelas II Pada Subtema Bermain Di Rumah Teman Di SD Negeri 124405 Pematang Siantar - Thasya Nadhira; Aprido Bernando Simamora; Canni Loren Sianturi (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research aims to determine the effect of Talking Stick learning media on the learning outcomes of class II students in the sub-theme of playing at friends' houses at SD Negeri 124405 Pematang Siantar odd semester FY 2023/2024. The type of research in this research is quantitative research. The research population was all class II A students at SD Negeri 124405 Pematang Siantar totaling 22 students. The sampling technique in this research is non-probability sampling, where the sample selected is a saturated sample. The sample in this study consisted of class II at state elementary school 124405 Pematang Siantar, totaling 22 students. The results of this research show that student learning outcomes using the contextual learning model with an average of 82.77. The results of the t distribution test at the significance level (ɑ = 0.05), dk = N-1 = 22-1 = 21, namely tcount>ttable, then the data has a t distribution with results of 13.97>ttable 0.404. The data can be said to have a significant influence. The results of the t-test table prove that there is an influence of the contextual learning model (X) on learning outcomes (Y) with a tcount of 13.97>ttable 0.404. This proves that there is a significant influence from the use of Talking Stick learning media on class II learning outcomes in the sub-theme of playing at a friend's house at SD Negeri 124405 Pematang Siantar.